Effects of age on memory for pragmatic implications in advertising: An eye movement study. (March 2021) - Yu, Jing; Peng, Xue-Rui; Yan, Ming
People employ automatic inferential processing when confronting pragmatically implied claims in advertising. However, whether comprehension and memorization of pragmatic implications differ between young and older adults is unclear. In the present study, we used eye-tracking technology to investigate online cognitive processes during reading of misleading advertisements. We found an interaction between age and advertising content, manifested as our older participants generated higher misleading rates in health-related than in health-irrelevant products, whereas this content-bias did not appear in their younger counterparts. Eye movement data further showed that the older adults spent more time processing critical claims for the health-related products than for the health-irrelevant products. Moreover, the correlations between fixation duration on pragmatic implications and misleading rates showed opposite trends in the two groups. The eye-tracking evidence novelly suggests that young and older adults may adopt different information processing strategies to comprehend pragmatic implications in advertising: More reading possibly enhances young adults' gist memory whereas it facilitates older adults' verbatim memory instead.